Enhancing oxytocin and prolactin levels to address oligogalactia through emotional management and massage in working mothers - Astuti, Dwi; Rahfiludin, Mohammad Z.; Dwidiyanti, Meidiana; Denny, Hanifa M. (Narra J, 2024)
Emotional management, combined with oxytocin massage and breast care, offers a comprehensive approach to boost prolactin release, enhance milk production, and improve breastfeeding outcomes. The aim of this study was to evaluate the effectiveness of combining emotional management with oxytocin massage and breast care in increasing oxytocin and prolactin hormone levels to address oligogalactia in working postpartum mothers. A quasi-experimental study was conducted at Kudus Community Health Center, Kudus Regency, Central Java, Indonesia, from January to March 2024. A total of 93 postpartum mothers were randomly assigned to three groups: (1) emotional management with oxytocin massage; (2) emotional management with breast care; and (3) lactation education only. Blood samples were collected before and after the interventions to measure oxytocin and prolactin levels. The present study found that emotional management combined with oxytocin massage significantly increased oxytocin levels from 505.0±264.0 pg/mL to 600.0±231.3 pg/mL (mean difference: 103 pg/mL; p=0.002) and prolactin levels from 191.0±67.3 ng/mL to 233.0±86.8 ng/mL (mean difference: 27 ng/mL; p=0.001). The emotional management and breast care group showed a smaller increase in oxytocin (362.0±175.1 pg/mL to 418.0±185.1 pg/mL; mean difference: 23 pg/mL; p=0.048) and a significant increase in prolactin (195.0±48.8 ng/mL to 255.0±82.3 ng/mL; mean difference: 38 ng/mL; p=0.049). In contrast, the lactation education group showed no significant changes in oxytocin (p=0.756) or prolactin levels (p=0.341). In conclusion, emotional management combined with oxytocin massage significantly increased both oxytocin and prolactin levels, suggesting that integrating emotional management and oxytocin massage may be an effective strategy for postpartum lactation support.